Precipitated silica and method for producing same

By developing characteristic precipitated silica, the problem of high surface area silica improving rolling resistance and wear resistance in polymer compositions but reducing wet grip is solved, achieving a balance of efficiently enhancing rolling resistance and wet grip performance in tires.

CN119873845APending Publication Date: 2025-04-25RHODIA OPERATIONS SAS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510125678.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-11-08
Filing Date
2019-11-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When high surface area silica is used in polymer compositions, although the rolling resistance and wear resistance of the tire can be improved, it often leads to a reduction in wet grip performance, making it difficult to find an effective compromise between the two.

Method used

A characteristic precipitated silica has been developed with a CTAB surface area of ​​160 m2/g or above, a median particle size measured by centrifugal sedimentation of more than 25000/|SCTAB|, and an aluminum content of no more than 4500 ppm. The silica is ensured by a specific preparation method, including controlling the pH value and adding the ratio of silicate and acid, ensuring its uniform dispersion and efficient enhancement in the polymer composition.

Benefits of technology

The precipitated silica provides good enhancement index and compound processability in the elastomer composition while exhibiting high hysteresis at low temperatures and low hysteresis at high temperatures, significantly improving the tire's rolling resistance and wet grip performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259836140000151
    Figure BDA0005259836140000151
  • Figure BDA0005259836140000211
    Figure BDA0005259836140000211
  • Figure BDA0005259836140000221
    Figure BDA0005259836140000221
Patent Text Reader

Abstract

The invention relates to precipitated silica and a method of making the same. A precipitated silica having a large particle size for use in tire applications.
Need to check novelty before this filing date? Find Prior Art

Description

This application is a divisional application of the invention patent application with the application date of November 6, 2019, application number 201980072076.6, and invention name “Precipitated silica and its manufacturing method”. Technical Field

[0001] The present invention relates to precipitated silica for use as reinforcing filler in elastomeric compositions. Background Art

[0002] The use of precipitated silica as a reinforcing filler in polymer compositions, in particular in elastomeric compositions, is known. Such use is very demanding: the filler should be easily and effectively incorporated and dispersed in the elastomeric matrix and typically form chemical bonds with one or more elastomers together with a coupling agent, thereby resulting in a high and uniform reinforcement of the elastomeric composition. Silica-filled elastomeric compositions are particularly advantageously used in tire formulations. Tire treads filled with so-called highly dispersible silicas have made it possible to achieve a compromise in properties in terms of rolling resistance, wear resistance and grip that cannot be obtained with conventional tire carbon blacks.

[0003] With high surface area (typically more than 160m 2 Precipitated silicas with a high surface area and a large particle size distribution are known. For example, WO 03 / 016215 A1 discloses precipitated silicas with a high surface area and a large particle size distribution.

[0004] WO 2013 / 092745 A1 discloses a method for preparing precipitated silica, the method comprising the following steps: (i) providing an aqueous raw material with a pH between 2 and 5; (ii) adding a silicate and an acid simultaneously to the raw material so that the pH of the reaction medium is maintained between 2 and 5; (iii) stopping the addition of the acid while continuing to add the silicate to the reaction medium until a pH value of the reaction medium between 7 and 10 is obtained; (iv) adding the silicate and the acid simultaneously to the reaction medium so that the pH of the reaction medium is maintained between 7 and 10; and (v) stopping the addition of the silicate while continuing to add the acid until a pH value of the reaction medium less than 6 is obtained, in which method, concentrated acid is used in at least part of step (ii). WO 2013 / 092745 A1 does not disclose the amount of silicate added to the reaction medium during step (ii) relative to the total amount of silicate required for the reaction. The amount that can be calculated from the exemplary method in WO 2013 / 092745 A1 is less than 50% of the total amount of silicate required for the reaction.

[0005] The advantage of using high surface area silica is primarily the possibility of increasing the number of silica-elastomer bonds and thus the level of reinforcement. In tire tread rubber compositions, therefore, compared to compositions having approximately 160 m2 Compared with conventionally used loadings of silica with a surface area of ​​100 g / g, the use of lower loadings of silica with a high surface area appears to be advantageous, particularly for improving the rolling resistance and wear resistance of tires.

[0006] However, this realization of improving tire wear characteristics using high surface area silica in rubber compositions can often result in a reduction in wet grip performance. In fact, the use of large surface area silica with small particle size means a reinforcement of the filler network and, therefore, can result in lower hysteresis and lower wet grip performance at low temperatures. Therefore, there is always a need for precipitated silica used as a reinforcing filler in polymer compositions that effectively compromises wet grip and rolling resistance performance without reducing the benefits in terms of tire wear performance. Summary of the invention

[0007] It has now been discovered that precipitated silica having a specific relationship between surface area and particle size provides a good balance of the following properties in elastomeric compositions: high hysteresis at low temperatures and low hysteresis at high temperatures at comparable reinforcement index (tensile properties) and compound processability.

[0008] The first object of the present invention is a precipitated silica, characterized in that: - Equal to or greater than 160m 2 CTAB surface area S / g CTAB ; - the median particle size d50 measured by centrifugal sedimentation such that: |d50|>25000 / |S CTAB |(I) in: |d50| represents the numerical value of the median particle size d50 measured by centrifugal sedimentation and expressed in nm, and |S CTAB | represents m 2 CTAB surface area S expressed in g CTAB the value of ; and - Aluminium content not exceeding 4500 ppm.

[0009] In the remainder of this document, the terms "silica" and "precipitated silica" may be used interchangeably to refer to precipitated silica.The term "particles" is used in this specification to refer to aggregates of primary silica particles.

[0010] CTAB surface area S CTAB is a measure of the external specific surface area as determined by measuring the amount of N-hexadecyl-N,N,N-trimethylammonium bromide adsorbed on the silica surface at a given pH.

[0011] CTAB surface area S CTABPreferably equal to or greater than 180m 2 / g. CTAB surface area S CTAB Can even be equal to or greater than 200m 2 / g.

[0012] CTAB surface area does not exceed 400m 2 / g, typically not exceeding 380m 2 / g. CTAB surface area S CTAB Can be lower than 350m 2 / g.

[0013] For elastomer reinforcement applications, the CTAB surface area S CTAB The favorable range is: from 160 to 400m 2 / g, from 180 to 400m 2 / g, from 180 to 380m 2 / g, preferably from 180 to 350m 2 / g, from 200 to 350m 2 / g, even from 220 to 330m 2 / g.

[0014] An important feature of the silica of the present invention is that for a given S CTAB Specifically, it has been found that at a given CTAB surface area S CTAB The median particle size of the silica of the present invention is higher than that measured on the precipitated silica of the prior art.

[0015] The expression term "particle" is used herein to refer to an aggregate of primary silica particles. The term particle is used to refer to the smallest aggregate of primary silica particles that can be broken by mechanical action. In other words, the term particle refers to an aggregate of indivisible primary particles.

[0016] It has been found that the median particle size d50 and the CTAB surface area S of the silica of the present invention are CTAB So that: |d50|>25000 / |S CTAB |(I).

[0017] In formula (I), |S CTAB | represents m 2 CTAB surface area S expressed in g CTAB The value of |S CTAB | is a dimensionless number. For example, if S CTAB The measured value is 200m 2 / g, then |S CTAB | is 200.

[0018] In formula (I), |d50| represents the numerical value of the median particle size d50 measured by centrifugal sedimentation and expressed in nm. By way of example, if the value of d50 measured by centrifugal sedimentation is 100 nm, then |d50| is 100. d50 represents the diameter below (or above) which 50% of the total mass of aggregates is found. Thus, d50 represents the median particle size of a given distribution, wherein the term "size" in this context is intended to be "diameter". |d50| is a dimensionless number.

[0019] From 200 to 400m 2 CTAB surface area S / g CTAB In the range of CTAB surface areas, the silica of the present invention is characterized by a median particle size d50 that is generally greater than 60 nm, even greater than 80 nm. In some cases, the d50 in the range of CTAB surface areas may be greater than 90 nm.

[0020] The d50 value of the silica of the present invention typically does not exceed 250 nm, more typically does not exceed 200 nm.

[0021] The silica of the present invention is generally characterized by aggregates of primary particles having, on average, the same size, i.e., a single median value as measured, for example, by electron microscopy (TEM) or small angle X-ray scattering (SAXS), rather than aggregates of primary particles having, on average, more than one different primary particle size. That is, the precipitated silica of the present invention is characterized by a population of primary particle sizes.

[0022] The precipitated silica of the present invention is also characterized by a broad particle size distribution. The parameter Ld determined by centrifugal sedimentation in a disc centrifuge as described in detail below is used to characterize the particle size distribution width. Ld is defined as follows: Ld=(d84-d16) / d50 where dn is the diameter below which n% of the total measured mass is found. Ld is a dimensionless number. The particle size distribution width Ld is calculated on the cumulative particle size curve.

[0023] The particle size distribution width Ld is at least 1.2, typically at least 1.3, preferably at least 1.4. The particle size distribution width Ld is not greater than 4.0, typically not greater than 3.5.

[0024] Advantageously, the particle size distribution width Ld of the silica of the present invention is in the range of from 1.2 to 3.5, even in the range of from 1.3 to 3.2. The particle size distribution width Ld of the silica of the present invention may be in the range of from 1.3 to 3.0, preferably in the range of from 1.4 to 3.0, more preferably in the range of from 1.5 to 2.8.

[0025] The precipitated silica of the present invention contains less than 4500 ppm of aluminum, typically less than 4000 ppm. The amount of aluminum is defined as the amount by weight of aluminum metal relative to the weight of the silica. The aluminum content in the silica of the present invention is usually no more than 3800 ppm, preferably no more than 3500 ppm. The aluminum content can be as low as 100 ppm.

[0026] Typically, the precipitated silica of the present invention is characterized as follows according to the ratio V (d5-d50) / V (d5-d100) The large pore volume distribution is defined as (d5-d50) represents the pore volume formed by pores with diameters between d5 and d50 and V (d5-d100) represents the pore volume formed by pores with diameters between d5 and d100, where dn is the pore diameter for which n% of the total surface area of ​​all pores is formed by pores with diameters larger than that diameter.

[0027] The silica of the present invention typically has a ratio V equal to or greater than 0.60, preferably equal to or greater than 0.65, or even equal to or greater than 0.70. (d5-d50) / V (d5-d100) Ratio V (d5-d50) / V (d5-d100) Typically no more than 1.20.

[0028] The BET surface area S of the silicon dioxide of the present invention is BET There is no particular limitation. BET surface area S BET Usually at least 160m 2 / g, at least 170m 2 / g. BET surface area S BET Up to 400m 2 / g, even up to 450m 2 / g.

[0029] Typically, the precipitated silica of the present invention is characterized by at least 30 m 2 / g difference (S BET -S CTAB ). Difference (S BET -S CTAB ) is not restricted. Generally speaking, the difference (S BET -S CTAB) less than 100m 2 / g.

[0030] The silica of the present invention is characterized by at least 4.0, even at least 4.5 N SiOH / nm2 Each nm 2 The number of silanols SiOH N SiOH / nm2 .

[0031] The second object of the present invention is a method for preparing the precipitated silica of the first object, the method comprising: (i) providing a starting solution having a pH of from 2.0 to 5.0, (ii) adding silicate and acid simultaneously to the starting solution so that the pH of the reaction medium is maintained in the range of from 2.0 to 5.0, (iii) stopping the addition of the acid and the silicate and adding a base to the reaction medium to raise the pH of the reaction medium to a value of from 7.0 to 10.0, (iv) adding silicate and acid simultaneously to the reaction medium such that the pH of the reaction medium is maintained in the range of from 7.0 to 10.0, (v) stopping the addition of the silicate while continuing to add the acid to the reaction medium to reach a pH of the reaction medium of less than 5.5 and obtaining a suspension of precipitated silica, wherein the amount of silicate added to the reaction medium during step (ii) is greater than 55% by weight of the total amount of silicate required for the reaction.

[0032] The total amount of silicate used to obtain a given final amount of silicon dioxide can be determined at the beginning of the process by a person skilled in the art according to common general knowledge.

[0033] The term "base" is used herein to refer to one or more than one base that can be added during the process of the method of the present invention, and it includes the group consisting of silicates as defined below. Any base can be used in the method. In addition to silicates, notable non-limiting examples of suitable bases are, for example, alkali metal hydroxides and ammonia.

[0034] The term "silicate" is used herein to refer to one or more than one silicate that may be added during the process of the method of the invention. The silicate is typically selected from the group consisting of alkali metal silicates. The silicate is advantageously selected from the group consisting of sodium silicate and potassium silicate. The silicate may be in any known form, such as a metasilicate or a disilicate.

[0035] In the case of use of sodium silicate, the latter generally has a SiO2 / Na2O weight ratio of from 2.0 to 4.0, in particular from 2.4 to 3.9, for example from 3.1 to 3.8.

[0036] The silicate may have a concentration (expressed as SiO2) of from 3.9 wt% to 25.0 wt%, for example from 5.6 wt% to 23.0 wt%, in particular from 5.6 wt% to 20.7 wt%.

[0037] The term "acid" is used herein to refer to one or more than one acid that may be added during the process of the method of the invention. Any acid may be used in the method. Typically, inorganic acids such as sulfuric acid, nitric acid, phosphoric acid or hydrochloric acid, or organic acids such as carboxylic acids, for example acetic acid, formic acid or carbonic acid are used.

[0038] The acid can be metered into the reaction medium in dilute or concentrated form. The same acid can be used in different concentrations at different stages of the process. Preferably, the acid is sulfuric acid.

[0039] In a preferred embodiment of the method, sulfuric acid and sodium silicate are used in all stages of the method. Preferably, the same sodium silicate, i.e. sodium silicate with the same concentration expressed as SiO2, is used in all stages of the method.

[0040] In step (i) of the method, a starting solution having a pH of from 2.0 to 5.0 is provided in a reaction vessel. The starting solution is an aqueous solution, and the term "aqueous" indicates that the solvent is water.

[0041] Preferably, the starting solution has a pH of from 2.5 to 5.0, especially from 2.8 to 4.4; for example, from 3.0 to 4.0.

[0042] The starting solution may be obtained by adding an acid to water so as to obtain the pH value as detailed above.

[0043] Alternatively, the starting solution may comprise a silicate. In this case, the starting solution may be obtained by adding an acid to a mixture of water and a silicate to obtain a pH of from 2.0 to 5.0.

[0044] The starting solution of step (i) may or may not contain an electrolyte. Preferably, the starting solution of step (i) contains an electrolyte.

[0045] The term "electrolyte" is used herein in its generally recognized meaning, i.e. to designate any ionic or molecular substance that decomposes or dissociates to form ions or charged particles when in solution. The term "electrolyte" is used herein to indicate that one or more than one electrolyte may be present. Mention may be made of electrolytes such as salts of alkali metals and alkaline earth metals. Advantageously, the electrolyte used in the starting solution is a salt of the metal and acid of the starting silicate used in the process. Notable examples are, for example, sodium chloride in the case of the reaction of sodium silicate with hydrochloric acid, or, preferably, sodium sulfate in the case of the reaction of sodium silicate with sulfuric acid. The electrolyte does not contain aluminum.

[0046] Preferably, when sodium sulfate is used as electrolyte in step (i), its concentration in the starting solution is from 8 to 40 g / L, especially from 10 to 35 g / L, for example from 10 to 30 g / L.

[0047] Step (ii) of the method comprises adding acid and silicate to the starting solution simultaneously. The rate of addition of acid and silicate during step (ii) is controlled in such a way that the pH of the reaction medium is maintained in the range of from 2.0 to 5.0. The pH of the reaction medium is preferably maintained in the range of from 2.5 to 5.0, in particular in the range of from 2.8 to 5.0, for example in the range of from 2.8 to 4.5.

[0048] The process of the invention is characterized in that the amount of silicate added during step (ii) is at least 55%, preferably at least 65% of the total amount of silicate required for the reaction.

[0049] Without being bound by theory, it is believed that the addition of at least 55% of the total amount required of silicate to the reaction mixture during step (ii) has the effect of increasing the median particle size d50 of the silica aggregates.

[0050] Preferably, step (ii) consists of the simultaneous addition of acid and silicate as detailed above.

[0051] In one embodiment of the process of the present invention, an intermediate step (ii') may be performed between step (i) and step (ii), wherein silicate and acid are added to the starting solution such that the pH of the reaction medium is maintained in the range of from 2.0 to 9.5. For all or only part of step (ii'), the addition of silicate and acid may be simultaneous. Step (ii') typically lasts 1 to 10 minutes, preferably 2 to 8 minutes, before step (ii) begins.

[0052] Next, in step (iii), the addition of acid and silicate is stopped and a base is added to the reaction medium. The addition of the base is stopped when the pH of the reaction medium reaches a value from 7.0 to 10.0, preferably from 7.5 to 9.5.

[0053] In a first embodiment of the process, the base is a silicate.Thus, in step (iii), the addition of the acid is stopped while the addition of silicate to the reaction medium continues until a pH of from 7.0 to 10.0, preferably from 7.5 to 9.5 is reached.

[0054] In a second embodiment of the process, the base is different from the silicate and is selected from the group consisting of alkali metal hydroxides, preferably sodium hydroxide or potassium hydroxide. When sodium silicate is used in the process, the preferred base may be sodium hydroxide.

[0055] Thus, in this second embodiment of the process, in step (iii), the addition of acid and silicate is stopped and a base other than silicate is added to the reaction medium until a pH of from 7.0 to 10.0, preferably from 7.5 to 9.5 is reached.

[0056] At the end of step (iii), i.e. after the addition of the alkali has been stopped, it may be advantageous to carry out a maturing step of the reaction medium. This step is preferably carried out at the pH obtained at the end of step (iii). The maturing step may be carried out while stirring the reaction medium. The maturing step is preferably carried out under stirring of the reaction medium within a time period of 2 to 45 minutes, in particular 5 to 25 minutes. Preferably, the maturing step does not include any addition of an acid or a silicate.

[0057] After step (iii) and the optional maturation step, simultaneous addition of acid and silicate is carried out such that the pH of the reaction medium is maintained in the range from 7.0 to 10.0, preferably from 7.5 to 9.5.

[0058] The simultaneous addition of acid and silicate (step (iv)) is typically carried out in such a way that the pH of the reaction medium is maintained equal to the pH reached at the end of the preceding step, step (iii) (within ± 0.2 pH units).

[0059] It should be noted that the process of the present invention may include additional steps. For example, between step (iii) and step (iv), and in particular between the optional aging step after step (iii) and step (iv), an acid may be added to the reaction medium. The pH of the reaction medium after the addition of this acid should be maintained in the range of from 7.0 to 9.5, preferably from 7.5 to 9.5.

[0060] In step (v), the addition of silicate is stopped while continuing to add acid to the reaction medium so as to obtain a pH value in the reaction medium of less than 5.5, preferably from 3.0 to 5.5, in particular from 3.0 to 5.0. A suspension of precipitated silica is obtained in the reaction vessel.

[0061] At the end of step (v), and therefore after the addition of acid to the reaction medium has been stopped, a maturation step may advantageously be carried out. This maturation step may be carried out at the same pH obtained at the end of step (v) and under the same time conditions as those described above for the maturation step that may optionally be carried out between steps (iii) and (iv) of the process.

[0062] The total amount of silicate required for the reaction includes silicate that may be present in the starting solution (step (i)), silicate that is added to the reaction medium during step (ii), step (ii') (when present), step (iv) and during step (iii) (when the base used to increase the pH in this step is a silicate).

[0063] The reaction vessel in which the entire reaction of the silicate with the acid takes place is usually equipped with appropriate stirring and heating equipment.

[0064] The entire reaction of silicate with acid (steps (i) to (v)) is generally carried out at a temperature of from 40 to 97°C, in particular from 60 to 95°C, preferably from 80 to 95°C, more preferably from 85 to 95°C.

[0065] According to one variant of the invention, the entire reaction of the silicate with the acid is carried out at a constant temperature generally ranging from 40 to 97°C, in particular from 80 to 95°C and even from 85 to 95°C.

[0066] According to another variant of the invention, the temperature at the end of the reaction is higher than the temperature at the beginning of the reaction: thus, the temperature at the beginning of the reaction (for example during steps (i) to (iii)) is preferably kept in the range from 40°C to 85°C, and the temperature is then increased, preferably to a value in the range from 80°C to 95°C, or even from 85°C to 95°C, at which value the temperature is kept (for example during steps (iv) and (v)) until the end of the reaction.

[0067] At the end of the steps just described, a suspension of precipitated silica is obtained which is subsequently separated (liquid / solid separation). The process typically comprises a further step (vi) of filtering the suspension and drying the precipitated silica.

[0068] The separation carried out in the preparation process according to the invention generally comprises filtration, followed by washing, if necessary. The filtration is carried out according to any suitable method, for example by a belt filter, a rotary filter, such as a vacuum filter, or, preferably, a filter press.

[0069] The filter cake is then subjected to a liquefaction operation, during which a mineral acid is added to the filter cake. The acid is selected from the group consisting of sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid. The acid is preferably sulfuric acid. The amount of mineral acid added to the filter cake during the liquefaction step is such that the pH of the final product, precipitated silica, is less than 5.5, preferably less than 4.5. The pH may even be less than 3.5, although it is usually not less than 3.0.

[0070] The term "liquefaction" is intended here to indicate a process in which a solid, ie a filter cake, is transformed into a fluid-like substance. After the liquefaction step, the filter cake is in a flowable, fluid-like form and the precipitated silica is in the form of a suspension.

[0071] The liquefaction step may include a mechanical treatment which results in a reduction in the granulometry of the silica in the suspension. The mechanical treatment may be performed by passing the filter cake through a high shear mixer, a colloid-type mill or a ball mill.

[0072] During the liquefaction step, an aluminum compound may be added to the filter cake, provided that the pH of the final product precipitated silica is less than 8.0, preferably less than 7.0, and that the total amount of aluminum in the precipitated silica does not exceed 4500 ppm.

[0073] The suspension of precipitated silicon dioxide obtained after the liquefaction step is preferably subsequently dried.

[0074] Drying can be carried out according to means known in the art. Preferably, drying is carried out by atomization. For this reason, any type of suitable atomizer can be used, in particular turbine, nozzle, hydraulic or two-fluid spray dryers. In general, when using a filter press to filter, a nozzle spray dryer is used, and when using a vacuum filter to filter, a turbo spray dryer is used.

[0075] When a nozzle spray dryer is used for the drying operation, the precipitated silica that can then be obtained is generally in the form of substantially spherical beads. After this drying operation, the recovered product can optionally be subjected to a grinding or micronizing step; the precipitated silica that can then be obtained is generally in the form of a powder.

[0076] When a turbo spray dryer is used for the drying operation, the precipitated silica that can then be obtained can be in the form of a powder.

[0077] Finally, the dried, ground or micronized product as previously indicated may optionally be subjected to an agglomeration step comprising, for example, direct compression, wet granulation (ie with a binder such as water, silica suspension, etc.), extrusion or, preferably, dry pressing.

[0078] The precipitated silica that can then be obtained by this agglomeration step is generally in the form of granules.

[0079] The precipitated silica according to the invention or obtained by the above-described process according to the invention can be used in a variety of applications.

[0080] For example, the precipitated silica of the present invention can be used as a catalyst support. It can be used as an absorbent for active materials, such as liquids, especially for use in foods, such as vitamins (vitamin E) or choline chloride. It can be used as a tackifier, a texturizing agent or an anti-caking agent, as a battery separator component, or as an additive for toothpaste, concrete, or paper.

[0081] However, the precipitated silicas of the present invention are particularly advantageously applicable for the reinforcement of natural or synthetic polymers and polymer blends thereof.

[0082] It was found that the elastomeric compositions containing the silica of the present invention have excellent potential in tire tread compositions relative to compositions comprising prior art precipitated silicas, particularly in greatly improving rolling resistance and wet grip properties while maintaining high levels of tire handling and wear properties.

[0083] Therefore, another object of the present invention is a composition comprising a silica according to the invention as defined above and at least one polymer.When referring to the polymers in the composition, the phrase "at least one" is used herein to indicate that one or more than one polymer of each type may be present in the composition.

[0084] The expressions "copolymer" and "terpolymer" are used herein to refer to polymers comprising repeating units derived from two and three monomer units, respectively, having different natures.

[0085] At least one polymer may be selected from thermosetting polymers and thermoplastic polymers. Notable non-limiting examples of thermosetting polymers include thermosetting resins such as epoxy resins, unsaturated polyester resins, vinyl ester resins, phenolic resins, epoxy acrylate resins, urethane acrylate resins, phenoxy resins, alkyd resins, urethane resins, maleimide resins, and cyanate resins.

[0086] Notable non-limiting examples of suitable thermoplastic polymers include styrene-based polymers such as polystyrene, (meth)acrylate / styrene copolymers, acrylonitrile / styrene copolymers, styrene / maleic anhydride copolymers, ABS; acrylic polymers such as polymethyl methacrylate; polycarbonates; polyamides; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyphenylene ether; polysulfones; polyaryletherketones; polyphenylene sulfide; thermoplastic polyurethanes; polyolefins such as polyethylene, polypropylene, polybutene, poly-4-methylpentene, ethylene / propylene copolymers, ethylene / α-olefin copolymers; copolymers of α-olefins and various monomers such as ethylene / vinyl acetate copolymers, ethylene / (meth)acrylate copolymers, ethylene / maleic anhydride copolymers, ethylene / acrylic acid copolymers; aliphatic polyesters such as polylactic acid, polycaprolactone, and aliphatic diol / aliphatic dicarboxylic acid copolymers.

[0087] The silica of the invention can advantageously be used as a reinforcing filler in elastomeric compositions. A preferred object of the present invention is therefore a composition comprising the silica of the invention and one or more elastomers, which preferably exhibits at least one glass transition temperature between -150°C and +300°C, for example between -150°C and +20°C.

[0088] The notable non-limiting examples of suitable elastomers are diene elastomers. For example, an elastomer derived from an aliphatic or aromatic monomer may be used, comprising at least one degree of unsaturation, such as, in particular, ethylene, propylene, butadiene, isoprene, styrene, acrylonitrile, isobutylene or vinyl acetate, polybutyl acrylate or a mixture thereof. It may also be mentioned that functionalized elastomers are elastomers functionalized by chemical groups (e.g., by being able to react chemically or unreacted functional groups with silicon dioxide surface) positioned along the macromolecular chain and / or at one or more of its ends, and halogenated polymers. It may be mentioned that polyamides, ethylene homopolymers and copolymers, propylene homopolymers and copolymers.

[0089] Mention may be made, among the diene elastomers, of, for example, polybutadiene (BR), polyisoprene (IR), butadiene copolymers, isoprene copolymers, or mixtures thereof, and in particular styrene / butadiene copolymers (SBR, in particular ESBR (emulsion) or SSBR (solution)), isoprene / butadiene copolymers (BIR), isoprene / styrene copolymers (SIR), isoprene / butadiene / styrene copolymers (SBIR), ethylene / propylene / diene terpolymers (EPDM), copolymers or terpolymers based on acrylonitrile, and also related functionalized polymers (for example having pendant polar groups or polar groups at the chain ends which are capable of interacting with silica).

[0090] Mention may also be made of natural rubber (NR) and epoxidized natural rubber (ENR).

[0091] The polymer composition may be vulcanized with sulfur, or crosslinked, in particular with peroxides or other crosslinking systems (eg diamines or phenolic resins).

[0092] In general, the polymer compositions additionally comprise at least one coupling agent and / or at least one covering agent; they may also comprise, in particular, antioxidants.

[0093] As non-limiting examples, as coupling agents, use may in particular be made of "symmetrical" or "asymmetrical" silane polysulfides; mention may more particularly be made of bis((C1-C4)alkoxy(C1-C4)alkylsilyl(C1-C4)alkyl)polysulfides (in particular disulfides, trisulfides or tetrasulfides), such as, for example, bis(3-(trimethoxysilyl)propyl)polysulfide or bis(3-(triethoxysilyl)propyl)polysulfide, such as triethoxysilylpropyltetrasulfide. Mention may also be made of monoethoxydimethylsilylpropyltetrasulfide. Mention may also be made of silanes containing masked or free thiol functions.

[0094] The coupling agent may be pre-grafted onto the polymer. It may also be used in the free state or grafted onto the surface of the silica. The coupling agent may optionally be combined with a suitable "coupling activator", i.e. a compound which, when mixed with the coupling agent, increases the effectiveness of the coupling agent.

[0095] The weight proportion of the silica of the invention in the polymer composition can vary within a fairly wide range. It generally accounts for from 10% to 200% by weight, especially from 20% to 150% by weight, in particular from 20% to 80% by weight, for example from 30% to 70% by weight. Alternatively, the weight proportion of the silica of the invention in the polymer composition can be from 40% to 120% by weight, for example from 60% to 110% by weight, of the amount of one or more polymers.

[0096] The silica according to the invention may advantageously constitute the entirety of the reinforcing inorganic filler and even the entirety of the reinforcing filler of the polymer composition.

[0097] The silica according to the invention may optionally be combined with at least one other reinforcing filler, such as, in particular, commercial highly dispersible silicas, such as, for example 1165MP, 1115MP or 1085MP (commercially available from Solvay); another reinforcing inorganic filler such as, for example, alumina, indeed even a reinforcing organic filler, in particular carbon black (optionally covered with an inorganic layer, such as that of silica). The silica according to the invention then preferably constitutes at least 50% by weight, indeed even at least 80% by weight, of the total amount of reinforcing filler.

[0098] Compositions comprising the precipitated silica of the present invention can be used to manufacture a number of articles. Non-limiting examples of articles comprising the silica of the present invention or the above-mentioned polymer composition are, for example, soles, floor coverings, gas barriers, flame retardant materials and also engineering parts, such as rollers for ropeways, seals for household appliances, seals for liquid or gas pipelines, seals for brake systems, pipes, sheaths (especially cable sheaths), cables, engine mounts, battery separators, conveyor belts, transmission belts or dampers. Advantageously, the silica of the present invention can be used to manufacture tires, especially tire treads, especially tire treads for light vehicles or heavy vehicles.

[0099] Should the disclosure of any patents, patent applications, and publications incorporated by reference into this application conflict with the description of the present application to the extent that it renders a term unclear, the present description shall take precedence.

[0100] The present invention will now be described in more detail with reference to the following examples, the purpose of which is merely illustrative and not limiting the scope of the present invention.

[0101] Analytical methods

[0102] The physicochemical properties of the precipitated silicas of the present invention were determined using the methods described below.

[0103] Determination of CTAB surface area

[0104] The CTAB surface area (S) was determined according to an internal method derived from standard NF ISO 5794-1, annex G. CTAB )value.

[0105] Determination of BET surface area

[0106] The BET surface area S is determined according to the Brunauer-Emmett-Teller method as detailed in standard NF ISO 5794-1, Annex E (June 2010) BET , with the following adjustments: the sample is pre-dried at 200°C ± 10°C; the partial pressure P / P used for measurement 0 Between 0.05 and 0.3.

[0107] Determination of particle size distribution and particle size by centrifugal sedimentation in a disc centrifuge (CPS)

[0108] The values ​​of d50, d16, d84 and Ld are determined by centrifugal sedimentation in a disc centrifuge using a centrifugal light transmission particle size analyzer model "CPS DC 24000UHR" sold by CPS Instruments. The instrument is equipped with the operating software supplied with the device (operating software version 11g).

[0109] Instruments used: For the measurement needs, the following materials and products were used: Ultrasonic system: 1500W generator model Sonics Vibracell VC1500 / VCX1500 equipped with 19mm probe (converter: CV154 + booster (part number: BHNVC21) + 19mm probe (part number: 630-0208)).

[0110] Analytical balance with an accuracy of 0.1 mg (e.g. Mettler AE260); Syringes: 1.0 ml and 2.0 ml with 20 ga needles; 50 mL tall glass beaker (SCHOTT DURAN: 38 mm diameter, 78 mm height); magnetic stirrer with 2 cm stirring bar; container for ice bath during sonication.

[0111] Chemicals: deionized water; ethanol 96%; sucrose 99%; dodecane, all from Merck; PVC reference standard from CPS Instruments; The peak maximum of the reference standard used should be between 200 and 600 nm (eg 237 nm).

[0112] Preparation of the disc centrifuge

[0113] For the measurements, the following parameters were established: For the calibration standard parameters, the information of the PVC reference transmitted by the supplier was used. × cps = centipoise

[0114] System Configuration

[0115] The measurement wavelength was set to 405 nm. The following run time option parameters were established: Force Baseline: yes Correction for Non-Stokes: no Additional software noise filtering: no Baseline drift display: Show Calibration method: external Each calibration sample: 1

[0116] All other software options remain as set by the instrument manufacturer.

[0117] Preparation of the disc centrifuge

[0118] The centrifuge disk was rotated at 24000 rpm during 30 min. A density gradient of sucrose (CAS n° 57-50-1) was prepared as follows:

[0119] In a 50 mL beaker, prepare a 24 wt % sucrose solution in water. In a 50 mL beaker, prepare an 8 wt % sucrose solution in water. Once both solutions are homogenized individually, use a 2 mL syringe to take a sample from each solution and inject it into the rotating disk in the following order: Sample 1: 1.8 mL of 24 wt% solution Sample 2: 1.6 mL of 24 wt% solution + 0.2 mL of 8 wt% solution Sample 3: 1.4 mL of 24 wt% solution + 0.4 mL of 8 wt% solution Sample 4: 1.2 mL of 24 wt% solution + 0.6 mL of 8 wt% solution Sample 5: 1.0 mL of 24 wt% solution + 0.8 mL of 8 wt% solution Sample 6: 0.8 mL of 24 wt% solution + 1.0 mL of 8 wt% solution Sample 7: 0.6 mL of 24 wt% solution + 1.2 mL of 8 wt% solution Sample 8: 0.4 mL of 24 wt% solution + 1.4 mL of 8 wt% solution Sample 9: 0.2 mL of 24 wt% solution + 1.6 mL of 8 wt% solution Sample 10: 1.8 mL of 8 wt% solution

[0120] Prior to each injection into the dish, both solutions were homogenized in the syringe by aspirating approximately 0.2 mL of air followed by brief manual agitation for a few seconds (ensuring that no liquid was lost).

[0121] These injections, with a total volume of 18 mL, were used to generate a density gradient that can be used to eliminate certain instabilities that may occur during the injection of the sample to be measured. To protect the density gradient from evaporation, we added 1 mL of dodecane in the rotating disk using a 2 mL syringe. The disk was then kept spinning at 24000 rpm for 60 min before any first measurement.

[0122] Sample preparation

[0123] 3.2g of silica is weighed into a 50mL tall glass beaker (SCHOTT DURAN: 38mm in diameter, 78mm in height) and 40mL of deionized water is added to obtain an 8wt% silica suspension. The suspension is stirred with a magnetic stirrer (minimum 20s), and the beaker is then placed in a crystallization dish filled with ice and cold water. The magnetic stirrer is taken out and the crystallization dish is placed under an ultrasonic probe, which is placed 1cm from the bottom of the beaker. The ultrasonic probe is set to 56% of its maximum amplitude and runs for 8min. At the end of the ultrasonic treatment, the beaker is again placed on a magnetic stirrer stirred at a minimum of 500rpm using a 2cm magnetic stirring bar until after sampling.

[0124] The ultrasonic probe should be in proper working condition. The following checks should be performed and if negative results are obtained, a new probe should be used: Visual inspection of the physical integrity of the probe tip (roughness depth less than 2 mm measured with a precision caliper); Commercial silica The measured d50 of 1165MP should be 93nm±3nm.

[0125] analyze

[0126] Prior to analyzing each sample, the calibration standards were recorded. In each case, 0.1 mL of a PVC standard provided by CPS Instruments and whose characteristics were previously entered into the software was injected. It is important that the measurement is started in the software simultaneously with this first injection of the PVC standard. By ensuring that the measurement is started simultaneously with the injection, confirmation of the device should have been received prior to the injection of 100 μL of the pre-sonicated sample.

[0127] These injections were done using 2 clean 1 mL syringes.

[0128] At the end of the measurement, which reaches the end point of the time required to settle all particles of smaller diameter (configured in the software to 0.02 μm), the ratio of each diameter category is obtained. The curve obtained is called the aggregate size distribution.

[0129] Results: The values ​​d50, d16, d84 and Ld are based on a distribution plotted on a linear scale. Integration of the particle size distribution function of the diameter allows obtaining the "cumulative" distribution, that is to say the total mass of particles between the smallest diameter and the diameter of interest. d50: is the diameter below and above which 50% of the population by mass is found. d50 is known as the median size, ie the diameter, of the silica aggregates. d84: is the diameter below which 84% of the total mass of the aggregate is measured. d16: is the diameter below which 16% of the total mass of the aggregate is measured. Ld: calculated according to the following formula: Ld = (d84-d16) / d50

[0130] Determination of pore volume and pore size by mercury porosimetry

[0131] Pore ​​volume and pore size distribution using Micromeritics IV 9520 porosimeter; they are calculated by the Washburn relation using a contact angle θ equal to 140° and a surface tension γ equal to 485 dynes / cm. Each sample is dried in an oven at 200° C. at atmospheric pressure for 2 hours before the measurement. The starting weight of the silica placed in the model 10 penetrometer (accuracy 0.001 g) is chosen for good reproducibility of the measurements in such a way that the “stem volume used”, i.e. the percentage mercury (Hg) volume consumed to fill the penetrometer, is from 40% to 80%. The penetrometer is then slowly evacuated to 50 μm of Hg and kept at this pressure for 5 min.

[0132] Operated with software version IV 1.09 The device was used. No correction was made to the raw data. The measurement range was from 3.59 kPa (0.52 psi) to 413685 kPa (60000 psi), and at least 100 measurement points were used (19 measurement points from 3.59 kPa (0.52 psi) to 193 kPa (28 psi), with a 10 second equilibrium time, and then 81 points from 1.93 kPa (0.28 psi) to 413685 kPa (60000 psi), with a 20 second equilibrium time). Where appropriate, the software introduced additional measurement points if the mercury injection volume increment was >0.5 mL / g. The mercury injection curve was smoothed by means of the "smooth differential" function of the device software.

[0133] Log Differential Intrusion (mL / g) versus pore size data were analyzed over the pore diameter range from 3.5 nm to 5 μm.

[0134] Determination of aluminum content

[0135] The amount of aluminum was measured using XRF wavelength dispersive X-ray fluorescence spectrometry (using a WDXRF Panalytical instrument). The ion exchange reaction was performed in a 4 cm diameter cell under helium using a 200 μm ion exchange reaction mixture covered with a thin Prolene film (4 μm ) in a cell containing silica powder. The following parameters were used to measure Al and Si fluorescence: Al Kα angle 2θ = 144,9468° (20 s), background signal angle 2θ = -1,2030° (4 s), Si Kα angle 2θ = 109,1152° (10 s), tube power 4 kW (32 kV, 125 mA), PE002 crystal and 550 μm collimator, gas flux detector.

[0136] per nm 2 Determination of the number of thiols

[0137] The amount of methanol grafted onto the silica surface was determined by 2 The number of thiols on the surface area is determined. First, in a stirred autoclave, 1 gram of silica is suspended in 10 mL of methanol. The sealed and insulated autoclave is heated to 200°C (40 bar) for 4 hours. The autoclave is then cooled in a cold water bath. The grafted silica is recovered by settling and the residual methanol is evaporated in a nitrogen stream. The grafted silica is vacuum dried at 130°C for 12 hours. The carbon content is determined by elemental analysis. 2 The thiol number is calculated using the following formula: N SiOH / nm2 =[(%Cg-%Cr)x6.023x10 23 ] / [S BET x10 18 x12x100] Wherein %Cg: mass percentage of carbon present on the grafted silica; and %Cr: mass percentage of carbon present on the original silica.

[0138] Examples

[0139] Example 1

[0140] 928 liters of process water were introduced into a 2500 liter reactor and heated to 90° C. 14.7 kg of solid sodium sulfate were introduced into the reactor with stirring, and sulfuric acid (concentration: 96 wt %) was then added until the pH reached a value of 4.2.

[0141] Sodium silicate solution (SiO2 / Na2O weight ratio: 3.43, density: 1.230 kg / L) and sulfuric acid (concentration: 7.7 wt%) were introduced into the reactor simultaneously at a flow rate of 352 L / h over a period of 50 minutes. The flow rate of the acid was adjusted so as to maintain the pH of the reaction medium at a value of 4.2. The amount of silicate added to the reaction medium was 79% of the total amount.

[0142] After 50 minutes, the introduction of acid was stopped and the addition of silicate was continued to bring the pH to 8.0. At the same time, the temperature was raised to 94° C. A further simultaneous addition was then carried out over a period of 7 minutes at a flow rate of 577 L / h of sodium silicate (the same as in the first simultaneous addition of sodium silicate) and a regulated flow rate of sulfuric acid (concentration: 7.7 wt %) in order to maintain the pH of the reaction medium at a value of 8.0.

[0143] After this simultaneous addition, the pH of the reaction medium is brought to a value of 4.8 by introducing sulfuric acid (concentration: 7.7 wt %) to obtain a suspension of precipitated silica. The suspension is filtered on a filter press and washed to obtain a precipitated silica cake with a solids content of 20.7 wt %. Then, in a reactor with continuous and vigorous stirring, 1360 grams of sulfuric acid solution (concentration: 7.7 wt %) are added to the obtained silica cake for a liquefaction step. The resulting slurry is dried by a nozzle spray dryer to obtain precipitated silica S1. The characteristics of precipitated silica S1 are reported in Table 1.

[0144] Example 2

[0145] 927 liters of process water were introduced into a 2500 liter reactor and heated to 90° C. 14.7 kg of solid sodium sulfate were introduced into the reactor with stirring, and then sulfuric acid (concentration: 96 wt %) was added until the pH reached a value of 4.1.

[0146] Sodium silicate solution (SiO2 / Na2O weight ratio: 3.43, density: 1.230 kg / L) and sulfuric acid (concentration: 7.7 wt%) were introduced into the reactor simultaneously at a flow rate of 352 L / h over a period of 50 minutes. The flow rate of the acid was adjusted so as to maintain the pH of the reaction medium at a value of 4.1. The amount of silicate added to the reaction medium was 78% of the total amount.

[0147] After 50 minutes, the introduction of acid was stopped and the addition of silicate was continued until the pH reached a value of 8.0. At the same time, the temperature was raised to 94° C. A further simultaneous addition was then carried out over a period of 7 minutes at a flow rate of 577 L / h of sodium silicate (the same as in the first simultaneous addition of sodium silicate) and a regulated flow rate of sulfuric acid (concentration: 7.7 wt %) in order to maintain the pH of the reaction medium at a value of 8.0.

[0148] After this second simultaneous addition, the reaction medium is brought to a pH of 4.7 by introducing sulfuric acid (concentration: 7.7 wt %) and a suspension of precipitated silica is obtained. The suspension is filtered on a filter press and washed to obtain a precipitated silica cake with a solids content of 19.5 wt %. The silica cake obtained is subjected to a liquefaction step by adding 1751 g of a sodium aluminate solution with an Al2O3 content of 22.5 wt % to the cake in a reactor with continuous and vigorous stirring. The resulting slurry is dried by a nozzle spray dryer to obtain precipitated silica S2. The properties of the precipitated silica S2 are reported in Table 1.

[0149] Comparative Example 1

[0150] 960 liters of water were introduced into a 2500 liter reactor and heated to 90° C. 15 kg of solid sodium sulfate were introduced into the reactor with stirring. Sulfuric acid (concentration: 96 wt %) was then added until the pH reached a value of 3.7.

[0151] Sodium silicate solution (SiO2 / Na2O weight ratio: 3.41, density: 1.231 kg / L) and sulfuric acid (concentration: 7.7 wt%) were introduced into the reactor simultaneously at a flow rate of 370 L / h over a period of 25 minutes. The flow rate of the acid was adjusted so as to maintain the pH of the reaction medium at a value of 3.7. The amount of silicate added to the reaction medium was less than 50% of the total amount of silicate required for the reaction.

[0152] After 25 minutes of simultaneous addition at 90° C., the introduction of acid was stopped and the pH of the reaction medium was brought to 8.0. At the same time, the temperature was raised to 94° C. A further simultaneous addition was then carried out over a period of 18 minutes at a sodium silicate flow rate of 600 L / h (the same as for the first simultaneous addition of sodium silicate) and at an adjusted flow rate of sulfuric acid (concentration: 7.7 wt %), in order to maintain the pH of the reaction medium at a value of 8.0.

[0153] After this simultaneous addition, the reaction medium is brought to a pH of 4.5 by introducing sulfuric acid (concentration: 7.7 wt %) and a suspension of precipitated silica is obtained. The suspension is filtered on a filter press and washed to obtain a precipitated silica cake with a solids content of 19.2 wt %. The silica cake is subjected to a liquefaction step by simultaneous addition of sulfuric acid (concentration: 7.7 wt %) and sodium aluminate solution (Al / SiO2 ratio: 0.30 wt %) to the cake in a reactor with continuous and vigorous stirring.

[0154] The liquefied cake was then spray dried using a nozzle atomizer to provide silica CS 1. The properties of silica CS 1 are reported in Table 1. Table 1

[0155] Example 3-5 - Comparative Example 2

[0156] The control composition CE2 comprises the silica CS1. The compositions E3 to E5 according to the invention comprise the silicas S1 and S2.

[0157] Compositions were prepared according to the formulations given in Table 2 below (components are expressed in parts by weight per 100 parts of elastomer (phr)). Table 2

[0158] Preparation of rubber composition: The method for preparing the rubber composition is carried out in three consecutive stages. The first and second mixing stages (non-production stages, NP1 and NP2) include thermomechanical processing at high temperatures, followed by a third mechanical processing stage (production stage, P3) at a temperature below 110°C. The latter allows the introduction of a vulcanization system. The first and second stages are carried out with the aid of an internal mixer (clean room volume: 380mL) with filling factors of 0.62 and 0.60, respectively, from Brabender. The initial temperature and rotor speed are fixed each time to achieve a mixed drop temperature of about 140°C-170°C. The duration of the first mixing stage is between 2 and 10 minutes. After cooling the mixture (temperature below 100°C), the second mixing stage allows the introduction of a vulcanization system (sulfur and accelerator). It is carried out on an open two-roll mixer preheated to 50°C. The duration of this stage is between 2 and 6 minutes. The final rubber composition is then calendered into a sheet form with a thickness of 2-3mm. An evaluation of the rheological properties of the uncured compound was first performed to monitor processability indicators. Once the cure characteristics were determined, the uncured compound was cured at the cure optimum (t98) and the mechanical and dynamic properties were measured.

[0159] The viscosity of the uncured composition

[0160] According to NF ISO289 standard, Mooney viscosity was measured at 100°C using a MV 2000 rheometer. After one minute of preheating, the torque value was read at 4 minutes (ML (1+4)-100°C). In addition, according to DIN 53529 standard, a strain sweep measurement from 0.9% to 50% was performed using a D-MDR 3000 rheometer at 100°C temperature and 1 Hz frequency. The results obtained with those two methods are shown in Table 3. Table 3 CE2 E3 E4 E5 ΔG'(0.9%-50%)-100℃(kPa)-NP1 2756 1993 2729 3531 ΔG'(0.9%-50%)-100℃(kPa)-NP2 1181 746 1245 1632 ML(1+4)-100℃(MU)-P3 106 97 112 116

[0161] As can be seen in Table 3, the uncured compositions according to the invention show lower (improved) Payne effect ΔG' (0.9%-50%) and lower (improved) Mooney viscosity ML (1+4) at comparable CTAB values ​​relative to silica CS1 from control CE2. Due to the higher CTAB surface area of ​​silica S2, the uncured composition E4 has slightly higher Mooney viscosity values ​​but comparable Payne effect values ​​ΔG' (0.9%-50%), reflecting comparable processability of the uncured compounds. It can be concluded that the processability of the unvulcanized rubber mixture containing the silica of the invention is comparable to that shown by compositions from the prior art containing high surface area silicas with equal CTAB surface areas.

[0162] Mechanical properties of the cured composition:

[0163] The Shore A hardness of the cured compositions (vulcanization time t98 at 170° C.) was measured according to ASTM D 2240. Values ​​measured after 3 seconds.

[0164] Uniaxial tensile tests were carried out on an INSTRON 5564 at a speed of 500 mm / min with H2 specimens according to NF ISO 37 standard. The moduli M100 and M300 (obtained at 100% and 300% strain, respectively) and the tensile strength are expressed in MPa; the elongation at break is expressed in %. The reinforcement index (RI) is calculated (defined as the ratio between the modulus obtained at 300% strain and the modulus obtained at 100% strain). The measured properties are summarized in Table 4. Table 4 CE2 E3 E4 E5 Hardness Shore A-3s(pts) 64 59 61 63 Modulus M100(Mpa) 2.1 2.3 2.4 2.6 Modulus M300(Mpa) 8.3 9.5 9.4 10.7 RI=M300 / M100 3.9 4.1 4.0 4.2

[0165] The results in Table 4 show that the use of silicas S1 and S2 at the same loading as silica CS1 provides compounds with lower Shore A hardness, higher modulus M300 and higher reinforcement index RI compared to composition CE2.

[0166] Increasing the loading of S1 (composition E5) to achieve the same Shore A hardness as composition CE2 leads to the same conclusion regarding the improved reinforcement potential of the silica of the invention.

[0167] Dynamic properties of cured compositions:

[0168] The dynamic properties were measured on a viscosity analyzer (Metravib DMA+1000) according to ASTM D5992.

[0169] Dynamic response of a compound cured under strain sweep conditions

[0170] According to the cycle, the parallelepiped sample (cross section 8mm) was subjected to a temperature of 40°C and a frequency of 10 Hz. 2 The 100 mm thick steel sheet (100 mm x 100 mm) was subjected to sinusoidal deformation under alternating double shear, with the forward cycle ranging from 0.1% to 50% and the return cycle ranging from 50% to 0.1%. The values ​​of the maximum loss factor (tan δmax), shear storage modulus (G'0.1%, G*12%) and Payne effect (G'0.1%-G'50%) were recorded during the return cycle. The results are shown in Table 5. Table 5 CE2 E3 E4 E5 G'0.1%(MPa) 3.7 2.6 2.9 3.2 G'0.1%-G'50%(MPa) 2.6 1.5 1.8 2.0 G*12%(MPa) 1.5 1.5 1.6 1.6 tanδmax 0.245 0.190 0.203 0.218

[0171] Compared to composition CE2, based on lower tanδmax and Payne effect (G' 0,1% -G' 50% ), compositions E3 and E4 according to the invention show significantly improved hysteresis characteristics at high temperature (40°C). Despite the higher silica S1 loading in composition E5, the tan δmax value remains substantially lower than that of composition CE2 of the prior art. Those indicators demonstrate that compositions E3 to E5 have excellent potential in tire tread compositions, especially in improving rolling resistance without deteriorating the handling (steering) performance (G*12%) of the tire.

[0172] Dynamic response of a compound cured under temperature sweep conditions

[0173] Under a temperature sweep from -45°C to +45°C (heating rate of +5°C / min), the parallelepiped specimens (cross section 8mm) were stretched under 1% alternating double shear sinusoidal deformation and a frequency of 10 Hz. 2 The dynamic response of the vulcanized rubber composition was measured at 100° (0.1°) and 70° (100°) of height (7 mm). The maximum loss factor (tan δmax) was then monitored. The results are summarized in Table 6: Table 6 CE2 E3 E4 E5 tanδmax 0.720 0.862 0.832 0.832 <![CDATA[T max (℃)]]> -26 -27 -27 -26

[0174] Compositions E3 and E4 according to the invention show significantly improved hysteresis characteristics at low temperatures by greatly increasing the maximum loss factor (tan δmax) compared to composition CE2. Despite the higher silica S1 loading in composition E5, the tan δmax value is improved compared to composition CE2 of the prior art.

[0175] The above-mentioned characterization studies demonstrate that the compositions containing the silicas S1 and S2 of the invention have excellent potential in tire tread compositions, in particular in terms of greatly improving rolling resistance and wet grip (at comparable levels of tire handling) without deteriorating wear properties and processability behavior.

Claims

1. A precipitated silica, characterized in that: - Equal to or greater than 160m 2 CTAB surface area S / g CTAB ; - a median particle size d50 measured by centrifugal sedimentation which does not exceed 250 nm and which is such that: |d50|>25000 / |S CTAB |(I) in: |d50| represents the numerical value of the median particle size d50 measured by centrifugal sedimentation and expressed in nm, and |S CTAB | represents m 2 The surface area of ​​CTAB represented by S CTAB the value of ; and - Aluminium content not exceeding 4500 ppm.

2. The precipitated silica according to claim 1, wherein The CTAB surface area S CTAB From 180 to 400m 2 / g range.

3. The precipitated silica according to claim 1, wherein The CTAB surface area S CTAB is from 200 to 350m 2 / g range.

4. The precipitated silica according to claim 1, wherein The CTAB surface area S CTAB is from 220 to 330m 2 / g range.

5. The precipitated silica according to claim 1, wherein The CTAB surface area S CTAB From 200 to 400m 2 / g, and the median particle size d50 is greater than 60nm.

6. The precipitated silica according to claim 1, wherein The CTAB surface area S CTAB From 200 to 400m 2 / g, and the median particle size d50 is greater than 80nm.

7. The precipitated silica according to claim 1, wherein The CTAB surface area S CTAB From 200 to 400m 2 / g, and the median particle size d50 is greater than 90nm.

8. The precipitated silica according to any one of claims 1 to 7, wherein The particle size distribution width Ld measured by centrifugal sedimentation is from 1.5 to 2.

8.

9. The precipitated silica according to any one of claims 1 to 7, wherein The BET surface area S BET The CTAB surface area S CTAB The difference is at least 30m 2 / g.

10. The precipitated silica according to any one of claims 1 to 7, wherein The particle size distribution width Ld measured by centrifugal sedimentation is from 1.5 to 2.8, and the BET surface area S BET The CTAB surface area S CTAB The difference is at least 30m 2 / g.

11. The precipitated silica according to any one of claims 1 to 7, wherein Aluminum content as low as 100ppm.

12. A composition comprising the precipitated silica of any one of the preceding claims and at least one elastomer.

13. An article comprising the composition of claim 12 in the form of a tire or a tire component.

Citation Information

Patent Citations

  • Method of preparing silicas, silicas with specific pore-size and / or particle-size distribution and the use thereof, in particular for reinforcing polymers

    WO2003016215A1

  • Precipitated-silica production method

    WO2013092745A1